2010
DOI: 10.1590/s0100-06832010000500018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and methane fluxes in south Brazilian gleysol as affected by nitrogen fertilizers

Abstract: SUMMARYIndex terms: nitrogen fertilization, environmental impacts, agriculture, greenhouse effect. RESUMO: FLUXOS DE ÓXIDO NITROSO E DE METANO EM GLEISSOLO INFLUENCIADOS PELA APLICAÇÃO DE FERTILIZANTES NITROGENADOS NO SUL DO BRASIL Fertilizantes nitrogenados incrementam os fluxos de óxido nitroso (N 2 O) e podem deprimir a oxidação de metano (CH 4 ) em solos agrícolas. Entretanto, não existem resultados da magnitude desses efeitos nas condições edafoclimáticas do Sul do Brasil, tampouco do potencial de alguma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
8
23
1
2
Order By: Relevance
“…The CH4 fluxes are more relevant in flooded soils where the incorporation of crop residues increases methanogenesis (ZSCHORNACK et al, 2011), but short-term CH4 emissions could also be verified in aerated soils following manure or nitrogen fertilizer amendments (SHERLOCK et al, 2002;ZANATTA et al, 2010). N2O emissions are critical on aerated soils under nitrogen fertilization or inclusion of legumes on the cropping systems (ESCOBAR et al, 2010;ZANATTA et al, 2010).…”
Section: As Avaliações Das Emissões De Dióxido De Carbono (Co 2 ) Mementioning
confidence: 99%
See 2 more Smart Citations
“…The CH4 fluxes are more relevant in flooded soils where the incorporation of crop residues increases methanogenesis (ZSCHORNACK et al, 2011), but short-term CH4 emissions could also be verified in aerated soils following manure or nitrogen fertilizer amendments (SHERLOCK et al, 2002;ZANATTA et al, 2010). N2O emissions are critical on aerated soils under nitrogen fertilization or inclusion of legumes on the cropping systems (ESCOBAR et al, 2010;ZANATTA et al, 2010).…”
Section: As Avaliações Das Emissões De Dióxido De Carbono (Co 2 ) Mementioning
confidence: 99%
“…N2O emissions are critical on aerated soils under nitrogen fertilization or inclusion of legumes on the cropping systems (ESCOBAR et al, 2010;ZANATTA et al, 2010).…”
Section: As Avaliações Das Emissões De Dióxido De Carbono (Co 2 ) Mementioning
confidence: 99%
See 1 more Smart Citation
“…In the same Ferralsol of the present study, Metay et al (2007) observed that N 2 O-N fluxes were positively related to increasing water-filled pore space. Zanatta et al (2010) found the highest fluxes of N 2 O-N during 45 days after soil management associated with high water-filled pore space and increased organic C and mineral N, which accounted for 30% of N 2 O-N emissions in a year. During two years of field experiment, Jantalia et al (2008) observed the highest fluxes of N 2 O-N after periods of high rainfall associated with mineral fertilization.…”
Section: Resultsmentioning
confidence: 94%
“…-and indirect ones -leaching, runoff, and atmospheric deposition (Cerri et al, 2009). Local assessment of GHG emissions from Brazilian agriculture systems have been reported (Carvalho et al, 2006;Metay et al, 2007;Jantalia et al, 2008;Zanatta et al, 2010;Cruvinel et al, 2011); however, the relative scarcity of data makes it difficult to assess the overall impact of irrigated common-bean under no-tillage on N 2 O-N and NH 3 -N fluxes in the Brazilian Cerrado.…”
Section: Introductionmentioning
confidence: 99%